Genetic structure and mating system of Euterpe edulis Mart. populations: A comparative analysis using microsatellite and allozyme markers - Conte R. (2008)
A comparative study between microsatellite and allozyme markers was conducted on the genetic structure and mating system in natural populations of Euterpe edulis Mart. Three cohorts, including seedlings, saplings, and adults, were examined in 4 populations using 10 allozyme loci and 10 microsatellite loci. As expected, microsatellite markers had a much higher degree of polymorphism than allozymes, but estimates of multilocus outcrossing rate (= 1.00), as well as estimates of genetic structure (FIS, G ST), were similar for the 2 sets of markers. Estimates of R ST, for microsatellites, were higher than those of GST, but results of both statistics revealed a close agreement for the genetic structure of the species. This study provides support for the important conclusion that allozymes are still useful and reliable markers to estimate population genetic parameters. Effects of sample size on estimates from hypervariable loci are also discussed in this paper. © The American Genetic Association. 2008. All rights reserved.